The rainbow bridge metaphor as a tool for developing accessible e-learning practices in higher education - Jane K Seale (The Canadian Network for Innovation in Education (CNIE), 2006)
This paper explores the extent to which existing accessibility metaphors can help to develop our conceptualizations of accessible e-learning practice in higher education and outlines a proposal for a new rainbow bridge metaphor for accessible e-learning practice. The need for a metaphor that reflects in more depth what we are beginning to understand about how to how to bring about that change, who should bring about that change, and what the result of such a change might be is identified. One such metaphor that could help us do this is the metaphor of a rainbow bridge. The stakeholders of accessible e-learning within higher education may understand the rainbow bridge as a useful metaphor in that the colours of the rainbow can represent all the main stakeholders in accessibility; the different views that different people can have of the same rainbow can represent different but related views of accessibility; and crossing the rainbow bridge to higher awareness can represent the awareness that is required in order to develop accessible e-learning practice.